The Impact of Online Gambling on Family Resilience: An Islamic Law Perspective from the Riau Region of Indonesia - Kusuma, Teddy; Husti, Ilyas; Aslati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study investigates the impact of online gambling on the resilience of Muslim families, with a particular focus on the Riau region of Indonesia, through the lens of Islamic law. The rapid growth of online gambling, driven by the accessibility and anonymity provided by digital technologies, has become a pressing concern for many families. This research explores how online gambling undermines family stability, contributing to financial distress, psychological stress, and familial conflict. Utilizing a qualitative approach, the study collects data through semi structured interviews, focus group discussions (FGDs), and document analysis from families affected by gambling, religious leaders, and law enforcement officials. Findings indicate that online gambling not only leads to significant financial losses, often resulting in the sale of personal assets and accruing debt, but also fosters emotional neglect and psychological turmoil within families. Moreover, the lack of legal enforcement against digital gambling exacerbates the issue, as international gambling platforms evade local jurisdiction. From an Islamic perspective, the study emphasizes the prohibition of gambling (maisir) in Islam and the importance of preserving family integrity, wealth, and mental health. The research suggests that Islamic education systems, particularly madrasahs and pesantren, play a vital role in preventing gambling addiction by promoting digital literacy, ethical decision making, and family values. The findings align with the objectives of maqāṣid al sharī‘ah the preservation of family unity, wealth, and mental well-being highlighting the need for integrated solutions combining legal, educational, and community-based interventions. This study contributes to the broader discourse on sustainable development, particularly in relation to SDG 16 (Peace, Justice, and Strong Institutions) and SDG 3 (Good Health and Well-being), by providing a comprehensive framework for addressing the rising threat of online gambling in Muslim communities.